Pengaruh Pendapatan dan Anggaran Belanja Terhadap Kapasitas Fiskal Pemerintah Daerah Kota Palopo - Ihwan Arifuddin (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2021)
Regional Revenue and Expenditure is an important factor in measuring the development of regional government so that the Fiscal Capacity of the Regional Government can be known, this aims to find out how much influence the Regional Revenue and Expenditure Budget has on the Fiscal Capacity of the Regional Government, especially in Palopo City. Researchers used quantitative research methods with associative research types. This research was conducted in the Regional Government of Palopo City, South Sulawesi Province. The population in this study is data on Regional Revenue, Regional Government Expenditures and Fiscal Capacity of Regional Governments, while the sample used is Regional Revenue and Regional Government Expenditures and the results of fiscal calculations for 10 years for the period 2011 to 2020. The analytical tool used is analysis Multiple Linear Regression using SPSS 18 and Eviews 10 Software. The results showed that Regional Income had an effect on Regional Fiscal Capacity in Palopo City and Regional Expenditures had a negative effect on Regional Fiscal Capacity in Palopo City.